Pengaruh Daya Tarik Wisata terhadap Keputusan Berkunjung ke Anjungan - Anggoro, Damas Aryo; Baskoro, Dimas Aryo (Prasetiya Mulya Publishing, 2024)
The purpose of this study is to determine the influence of tourist attraction to the decision to visit the tourist attraction. This research uses quantitative approach method, data analysis in this research is by using descriptive statistical analysis, with the nature of wanting to test the truth of a hypothesis made through the collection of primary data and secondary data, in order to predict and explain the relationship or influence of one variable to another.The effect of tourist attraction on guest decisions has a strong relationship. This result with a result of 0.601 shows a strong tourist attraction to the decision to visit the tourist attraction. Analysis by calculating the determination to know the strong influence given by the tourist attraction to the holiday decision, that is by squaring that happened. From the result show R Square = 0,361 or equal to 36,1% owned by tourist attraction and the remaining 63,9% owned by other variable which not examined and the conclusion obtained that the variable of tourist attraction has a strong influence on the decision to visit the the tourist attraction.